PENGGUNAAN AMPAS SAGU TERHADAP PERFORMANS JANGKRIK (Gryllidae sp) - Siti Dharmawati; Neni Widaningsih (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2017)
The aim of this study was to feed crickets that are more economical for farmer.byusing  localingredients feed  found in surrounding environment such as sago meal waste.The target outcomes to be achieved in this study is a scientific article. The hypothesis in this study  isthe use of sagomeal  waste  did not affect the was growth  of local cricket .  The method used in this studya completely randomized design using sago meal  waste in ration    for 0%, 5%, 10%, 15% and 20%. The variables observed in this study feed intake, weight gain, feed conversion and final body weight. The results showed that use of the of sago in the ration does not affect theSiignificance of the performances crickets instar phase. Sago meal waste can be used up to 20% in the ration of crickets. Keywords :  Sago meal waste, Performance,  Cricket